2022
DOI: 10.1001/jamanetworkopen.2022.16393
|View full text |Cite
|
Sign up to set email alerts
|

A Prehospital Triage System to Detect Traumatic Intracranial Hemorrhage Using Machine Learning Algorithms

Abstract: Key Points Question Can machine learning algorithms be used to triage patients with head trauma according to their severity before transportation? Findings In this cohort study of 2123 patients with head trauma, a machine learning–based prediction model detected traumatic intracranial hemorrhage with a sensitivity of 74% and a specificity of 75% by using only the patient’s prehospital information. Meaning This study suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Thirdly, whereas machine learning-based models frequently rely on a large number of variables the present models rely exclusively on a few, rapidly and easily available pre-hospital variables in daily practice and make it suitable for a decision-making tool. Fourthly, our results are consistent with a recent study by Abe et al In this study, ML algorithms have achieved the same performance as our model (AUC: 0.78) in detecting intracerebral hemorrhage after traumatic brain injury [ 18 ]. Finally, this study provides information on the “black box” of the model through Shapley values in order to ensure explainability for clinicians and increase acceptance.…”
Section: Discussionsupporting
confidence: 92%
“…Thirdly, whereas machine learning-based models frequently rely on a large number of variables the present models rely exclusively on a few, rapidly and easily available pre-hospital variables in daily practice and make it suitable for a decision-making tool. Fourthly, our results are consistent with a recent study by Abe et al In this study, ML algorithms have achieved the same performance as our model (AUC: 0.78) in detecting intracerebral hemorrhage after traumatic brain injury [ 18 ]. Finally, this study provides information on the “black box” of the model through Shapley values in order to ensure explainability for clinicians and increase acceptance.…”
Section: Discussionsupporting
confidence: 92%
“…Following the primary search, 1,405 studies were recognized after removing duplicated studies. At last, after screening the title, abstract, and full paper, twenty-six retrospective and three prospective, and two retrospective/prospective studies were included [ 20 50 ]; then, twenty-nine studies were included in the final quantitative analysis, and the other studies were excluded because no diagnostic accuracy was reported ( Fig. 1 ) [ 20 26 , 28 46 , 48 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…At last, after screening the title, abstract, and full paper, twenty-six retrospective and three prospective, and two retrospective/prospective studies were included [ 20 50 ]; then, twenty-nine studies were included in the final quantitative analysis, and the other studies were excluded because no diagnostic accuracy was reported ( Fig. 1 ) [ 20 26 , 28 46 , 48 52 ]. The machine learning networks were classified into, Support vector machine (SVM), Random Forest (RF), k-nearest neighbors’ algorithm (k-NN), VGG-16, Logistic Regression (LR), ResNet-18, AlexNet, DenseNet-121, eXtreme Gradient Boosting (XGBoost), Decision Tree (DT), and Deep Learning (DL) included Convolutional Neural Network (CNN); ResNet34, ResNet50, ResNet18, ResNet-v2, GoogleNet ( Table 1 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Shapley values have been adopted to interpret feature importance 20 , 22 , 29 , 38 and feature importance based on the XGBoost model was ranked with the aid of Shapley values. For easy and ready usage in clinical practice, previous studies have built machine learning models using only several top features 30 , 39 , 40 . For our XGBoost model, the top 4 features are CCM volume, presence of ICH, CCM at brain stem, and age at diagnosis, with which we try to build 4-Elements model.…”
Section: Discussionmentioning
confidence: 99%